An In Vitro Study of the Antimicrobial Effects of Indigo Naturalis Prepared from Strobilanthes formosanus Moore - Yin-Ru Chiang; Ann Li; Yann-Lii Leu; Jia-You Fang; Yin-Ku Lin (Molecules, 2013)
Indigo naturalis is effective in treating nail psoriasis coexisting with microorganism infections. This study examines the antimicrobial effects of indigo naturalis prepared from Strobilanthes formosanus Moore. Eight bacterial and seven fungal strains were assayed using the agar diffusion method to examine the effects of indigo naturalis and its bioactive compounds. The bioactive compounds of indigo naturalis were purified sequentially using GFC, TLC, and HPLC. Their structures were identified using mass spectrometry and NMR spectroscopy. UPLC-MS/MS was applied to compare the metabolome profiles of indigo naturalis ethyl-acetate (EA) extract and its source plant, Strobilanthes formosanus Moore. The results of in vitro antimicrobial assays showed that indigo naturalis EA-extract significantly (≥1 mg/disc) inhibits Gram-positive bacteria (Staphylococcus aureus, S. epidermis and methicillin-resistant S. aureus (MRSA)) and mildly inhibits non-dermatophytic onychomycosis pathogens (Aspergillus fumigates and Candida albicans), but has little effect on dermatophyes. Isatin and tryptanthrin were identified as the bioactive compounds of indigo naturalis using S. aureus and S. epidermis as the bioassay model. Both bioactive ingredients had no effect on all tested fungi. In summary, indigo naturalis prepared from Strobilanthes formosanus Moore exhibits antimicrobial effects on Staphylococcus and non-dermatophytic onychomycosis pathogens. Tryptanthrin and isatin may be its major bioactive ingredients against Staphylococcus and the inhibitory effect on MRSA may be due to other unidentified ingredients.